2020
DOI: 10.1149/1945-7111/aba7d9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Pd@Pd(OH)2 Core-Shell Nanoparticles onto Glassy Carbon from a Deep Eutectic Solvent (Reline) and their Use as Electrocatalyst for the Methanol Oxidation Reaction

Abstract: Pd@Pd(OH) 2 core-shell nanoparticles were potentiostatically electrodeposited onto a glassy carbon electrode, GCE, from Pd(II) ions dissolved in the reline deep eutectic solvent. It is shown that the GCE/Pd@Pd(OH) 2 -modified electrode displays a high catalytic activity towards the methanol electrochemical oxidation reaction (MOR) in alkaline solution, revealing a mass activity of (2370 ± 450) mA mg Pd −1 at the peak potential (for CVs recorded at 0.1 V s −1 ), much greater than those reported to date for othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…residual water reduction) is occurring on the diffusion-controlled growing surfaces of 3D nuclei of the new phase (i.e. Ni, 16 Fe, 18 Al, 19,20 Pd, 21,22 Cr, 23,24 Co 29,32 ). Considering all these features, the model proposed by Mejía-Caballero et al, 23 will be used for the analysis of the plots in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…residual water reduction) is occurring on the diffusion-controlled growing surfaces of 3D nuclei of the new phase (i.e. Ni, 16 Fe, 18 Al, 19,20 Pd, 21,22 Cr, 23,24 Co 29,32 ). Considering all these features, the model proposed by Mejía-Caballero et al, 23 will be used for the analysis of the plots in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, DES are friendlier with the environment and are more affordable. Furthermore, from DES the electrochemical nucleation and growth of MeNPs of Ni, 16 Fe, 17,18 Al, 19,20 Pd, 6,7,21,22 Cr, 23,24 and alloys (Ni-Co) 25 can be achieved. Due to the above mentioned, this work will deal with the mechanism and kinetics of the electrochemical nucleation and growth of AuNPs onto a GCE, from Au(III) ions dissolved in reline (DES formed by the eutectic mix of choline chloride and urea), and its influence on the electrochemical quantification of DA in presence of one its major interferents, uric acid (AU).…”
mentioning
confidence: 99%
“…20 To further verify the above hypothesis, malonic acid was introduced to [ChCl:2EG] (in which the lack of acid caused unsuccessful conversion of SnO Because the DESs are hydroscopic, the presence of residual water in the DESs can affect the electrochemical behavior of species in the DESs. [38][39][40][41][42][43] On one hand, the presence of small amounts of water in the DES can be beneficial by reducing the viscosity and thus increasing the conductivity and mass transport rate. 38,39 On the other hand, the reduction of the water in the DES produces hydroxide ions which could react with metal ions forming metal hydroxide precipitates and results in limits [40][41][42][43] or self-terminating 44 growth of the metal deposits.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41][42][43] On one hand, the presence of small amounts of water in the DES can be beneficial by reducing the viscosity and thus increasing the conductivity and mass transport rate. 38,39 On the other hand, the reduction of the water in the DES produces hydroxide ions which could react with metal ions forming metal hydroxide precipitates and results in limits [40][41][42][43] or self-terminating 44 growth of the metal deposits. In the present study, the formation of tin hydroxide precipitates could be compensated by the proton ions in the [ChCl:2MalA] DES which react with the hydroxide ions.…”
Section: Resultsmentioning
confidence: 99%
“…Palomar-Pardavé et al prepared Pd@Pd(OH) 2 core-shell nanoparticles in DES. It is shown that the GCE (glassy carbon electrode)/Pd@Pd(OH) 2 -modified electrode displays a high catalytic activity towards the MOR in alkaline solution [ 37 ]. Fan et al have prepared high-performance Pt-based alloy catalysts by chemical reduction or electrochemistry method in DES that plays an important role in controlling the shape of the nanoparticles [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%